2015
DOI: 10.1007/s00412-015-0546-5
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the interchromosomal network during keratinocyte differentiation

Abstract: The well-established human epidermal keratinocyte (HEK) differentiation model was investigated to determine possible alterations in chromosome territory (CT) association during differentiation. The seven human chromosomes (1, 4, 11, 12, 16, 17, and 18) selected for this analysis are representative of the chromosome size and gene density range of the overall human genome as well as including a majority of genes involved in epidermal development and differentiation (CT1, 12, and 17). Induction with calcium chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 66 publications
2
17
0
Order By: Relevance
“…In addition, five of nine CT examined showed significant differences in radial position between normal breast epithelial cells and a corresponding malignant cell line . Even more striking, it was reported that the radial positioning of seven CT in undifferentiated human keratinocytes strongly correlated with gene density, while the positioning in the corresponding CT from late differentiating keratinocytes were highly altered with no relationship to gene density or chromosome size . These findings are consistent with the probabilistic radial positioning code proposed by Cremer and associates and support the view that the probabilistic positioning code is cell‐type‐specific and can undergo alterations during both malignant progression and cell differentiation where massive changes in the genomic expression programs generally occur.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition, five of nine CT examined showed significant differences in radial position between normal breast epithelial cells and a corresponding malignant cell line . Even more striking, it was reported that the radial positioning of seven CT in undifferentiated human keratinocytes strongly correlated with gene density, while the positioning in the corresponding CT from late differentiating keratinocytes were highly altered with no relationship to gene density or chromosome size . These findings are consistent with the probabilistic radial positioning code proposed by Cremer and associates and support the view that the probabilistic positioning code is cell‐type‐specific and can undergo alterations during both malignant progression and cell differentiation where massive changes in the genomic expression programs generally occur.…”
Section: Introductionsupporting
confidence: 85%
“…Figure depicts typical CT multicolor labeled images from re‐FISH experiments with MCF10 normal human breast and malignant breast cancer cells (Figure A,B ), undifferentiated and differentiated human keratinocytes (Figure C,D), WI38 normal human fibroblasts (Figure E), and the NOR‐CT in WI38 cells (Figure F). An integrated computer imaging program was then applied to segment the individual CT and determine a large battery of measurements among the total population of labeled CT in the individual nuclei . These measurements included the 3‐D nearest neighbor distances between the borders of all labeled CT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FISH was performed as described previously (Sehgal et al 2016) on MCF-10A cells induced to express either shSCRAM or shSMARCA4 shRNAs. Probes from bacterial artificial chromosomes RP11-82D16 for Chr 1p, RP11-81J5 for Chr 1q, RP11-81L5 for Chr 4p; and RP11-196K19 for Chr 4q were used.…”
Section: Dna Fluorescence In Situ Hybridization (Fish)mentioning
confidence: 99%
“…Chromosome positioning is not a constant feature of nuclei as positional changes were recorded during keratinocyte differentiation (Sehgal et al, ), during adipocyte differentiation (Charó, Rodríguez Ceschan, Galigniana, Toneatto, & Piwien‐Pilipuk, ; Kuroda et al, ), after PHA‐activation of lymphocytes (Ioannou, Kandukuri, Simpson, & Tempest, ), and after serum deprivation/stimulation (Mehta, Amira, Harvey, & Bridger, ). It thus appears that the nuclear organization of the genome is directly associated with its cellular function.…”
Section: Introductionmentioning
confidence: 99%